Implementation of Criminal Sanctions Against Foreign Narcotics Courier Performers - Zainab Ompu Jainah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Criminal sanctions that regulate narcotics crimes have emphasized the sanctions that will be given to anyone who violates them, ranging from rehabilitation to the death penalty. However, there are still many who commit these violations, until now, there are various forms of modus operandi for committing a criminal act in distributing narcotics. Perpetrators do not run out of wits to do all kinds of ways to achieve their goals. This mode is developed because law enforcement officers are intensively carrying out prevention efforts to eradicate narcotics crimes. One form of the mode that is carried out is through drug intermediaries or couriers, by neatly wrapping and inserting into plastic capsules, stored in boxes or cans, tucked in candy or food, to places that have been specially designed so as not to be penetrated by detection equipment. The perpetrators of these drug couriers are not only carried out by Indonesian nationals, but have also been carried out between foreign countries through foreign nationals. Narcotics distribution is carried out in various ways through land, sea and air transportation. From the various modes carried out by the perpetrators of drug couriers, it is not uncommon for them to be unsuspected so that they can escape various forms of examination by the authorized law enforcement officers.